The antecedents of e-relationship quality in Online Travel Agency (OTA) at Kota Kinabalu - Nornasha Justin (2014)
The purpose of this study is to examine the relationships between antecedents of e-relationship quality, e-satisfaction, a-trust and e-loyalty in the context of Online Travel Agency (OTA) website services. The study also examines the mediating effect of e-satisfaction and e-trust on the relationship between antecedents of e-relationship quality and e-loyalty, as well as the mediating effect of e-satisfaction and e-trust. In this study, the antecedents of e-relationship quality are consists of communicational function, transactional function and relational function. Data from 191 respondents were used by analyzed with SPSS version 22. Multiple regressions analysis has been done and the result showed all of dimensions in antecedents of e-relationship quality have relationship with e-satisfaction, a-trust and e-loyalty. Furthermore, e-satisfaction and a-trust has significant with e-loyalty. The hierarchical regression analysis results indicated that e-satisfaction and a-trust mediated the relationships between antecedents of e-relationship quality consists of communicational function, transactional function and relational function and e-loyalty. E-satisfaction and a-trust also partially mediates the relationship between communicational function, transactional function and relational function and e-loyalty. Thus, as marketers and Online Travel Agency (OTA), they need to take suitable marketing plan in order to achieve e-satisfaction and a-trust and loyalty. Limitation of the study and future research recommendation also been done.